Promoting school readiness in children with developmental disabilities in LMICs - Nair, M. K. C.; Radhakrishnan, Rekha; Olusanya, Bolajoko O. (Frontiers in Public Health, 2023)
The United Nations' Sustainable Development Goals (SDGs) explicitly acknowledge inclusive and equitable quality education as the primary goal of any global initiatives for early childhood development for children under 5 years with developmental delays and disabilities. Primary education provides the foundation for lifelong learning, vocational attainment, and economically independent living. Globally, the majority (over 90%) of children with developmental disabilities reside in low- and middle-income countries (LMICs). These children are significantly less likely to have foundational reading and numeracy skills, more likely to have never attended school and more likely to be out of primary school, compared to children without disabilities. Concerted and well-coordinated efforts to prepare these children in early childhood for inclusive education constitute a moral and ethical priority for all countries. This paper sets out to examine the concept and dimensions of school readiness for children under 5 years from an extensive narrative review of the literature. It identifies the barriers and challenges for school readiness for children with disabilities and the limitations of the available tools for evaluating school readiness. It concludes by emphasizing the critical role of inter-disciplinary engagement among pediatric caregivers in promoting school readiness in partnership with the families and community where the children reside. Overall, the paper highlights the need for appropriate policy initiatives at the global and national levels to promote school readiness specifically for children under 5 years with developmental disabilities in LMICs, if the aspirational goal of inclusive education by 2030 under the SDGs is to be realized.